TWO NEW CALOGLYPHUS BERLESE MITES (ASTIGMATA: ACARIDAE) RECORDED IN PAKISTAN (Biological Sciences - PJSIR, 2004)
The taxonomy of Caloglyphus clemens and C. cingentis was studied. These species were encountered from two different host materials. A key for all the known hypopodes from Pakistan, their comparison of characters, similarity matrix and phenogram have been included.